حقیقیت سے متعلق قواعد اصولیہ سے اخذ احکام میں امام جصاص اور قاضی ابن العربی کا منہج: The Methodology of Imam Jassas and Qazi Ibn al-Arabi in Deriving Rulings from Principles Related to Haqeeqat - Hafiz Muhammad Umar Farooq; Dr Ahmad Raza (Al Manhal Research Journal, 2024)
In our daily conversations, we use various words and speak in different contexts. Sometimes, we take words in their literal meaning, and at other times, we understand them in a figurative sense. For instance, when a person dies in a road accident, it is often said that the driver "killed" him. Here, attributing the act of killing to the driver is figurative because only Allah has the power to give life and death. Similarly, in the Arabic language, literal (Haqeeqi) and figurative (majazi) meanings are also used. Since the Quran was revealed in eloquent Arabic, these language skills are found abundantly in it. For example, we see that the act of creation is often attributed to Allah in the Quran, which is literal and refers to the actual meaning of creation. However, in one or two instances, the act of creation is also attributed to Prophet Jesus (Isa), peace be upon him. When the word "creation" is used for Allah, it is in the literal sense, but when used for Prophet Jesus, it is figurative. Similarly, the word "Lord" (Rabb) is used for Allah, but in the story of Prophet Yusuf, it is also used for a king or master. In the first case, it is literal, while in the second, it is figurative. The commentators of the Quran have taken these linguistic and idiomatic principles into account in their interpretations. Over time, these principles have been formalized into rules. Considering these rules related to literal meanings (Haqeeqat), the tafaseer of Imam Jassas and Qadi Ibn al-Arabi have been studied in this article.